2014
DOI: 10.1186/1471-2415-14-18
|View full text |Cite
|
Sign up to set email alerts
|

Toxic optic neuropathy in the setting of docetaxel chemotherapy: a case report

Abstract: BackgroundTo describe the first reported case of toxic optic neuropathy secondary to docetaxel (Taxotere®) chemotherapy.Case presentationA 53-year-old female presented with predominantly unilateral visual loss, but extensive bilateral visual field defects and bilateral optic nerve head swelling 2 weeks after first dose of docetaxel (Taxotere®) and trastuzumab (Herceptin®) chemotherapy for a left sided node-positive, HER2 positive breast cancer. Extensive investigation ruled out other causes of optic neuropathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…33 Optic neuropathy has also been associated with DTX and PTX. 24,25,[49][50][51][52] Scaioli et al 52 reported that the most likely mechanism of the visual symptoms and electrophysiological changes caused by PTX use was vascular dysregulation in the retina or ischemia involving the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Optic neuropathy has also been associated with DTX and PTX. 24,25,[49][50][51][52] Scaioli et al 52 reported that the most likely mechanism of the visual symptoms and electrophysiological changes caused by PTX use was vascular dysregulation in the retina or ischemia involving the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Eye disorders, such as watering eyes (epiphora), lacrimal duct obstruction, and cystoid macular edema, have also been reported. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Watering eyes and lacrimal duct obstruction have been frequently reported. [10][11][12][13][14][15][16][17][18][19][20] Intravenously administered DTX is distributed to the tear fluid from the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…10 Toxic ON related to docataxel has been previously reported. 11,12 In those cases, symptoms related to ON, such as constriction of visual fields, loss of visual acuity and loss of colour vision started within the first few cycles, gradually worsening over weeks in a subacute fashion. Detailed evaluations including brain and orbital MRIs excluded other aetiologies.…”
Section: Discussionmentioning
confidence: 99%
“…One case report linked a patient's loss of vision to optic nerve damage during infusion of the taxane drug, docetaxel. This damage was reversed with high-dose steroid therapy (Moloney et al, 2014); however, not all visual changes after chemotherapy are reversible. Another study reported optic neuropathy and retinopathy in 5 patients with permanent visual damage (Khawly et al, 1996).…”
Section: Introductionmentioning
confidence: 94%